The Systematic Review and Meta-Analysis on the Immunogenicity and Safety of the Tuberculosis Subunit Vaccines M72/AS01E and MVA85A - Ullah, Inayat; Bibi, Shaheen; Ul Haq, Ijaz; Safia,; Ullah, Kifayat; Ge, Long; Shi, Xintong; Bin, Ma; Niu, Hongxia; Tian, Jinhui; Zhu, Bingdong (Frontiers in Immunology, 2020)
Background: Tuberculosis (TB) is a severe infectious disease with devastating effects on global public health. No TB vaccine has yet been approved for use on latent TB infections and healthy adults. In this study, we performed a systematic review and meta-analysis to evaluate the immunogenicity and safety of the M72/AS01E and MVA85A subunit vaccines. The M72/AS01E is a novel peptide-based vaccine currently in progress, which may increase the protection level against TB infection. The MVA85A was a viral vector-based TB subunit vaccine being used in the clinical trials. The vaccines mentioned above have been studied in various phase I/II clinical trials. Immunogenicity and safety is the first consideration for TB vaccine development. Methods: The PubMed, Embase, and Cochrane Library databases were searched for published studies (until October 2019) to find out information on the M72/AS01E and MVA85A candidate vaccines. The meta-analysis was conducted by applying the standard methods and processes established by the Cochrane Collaboration. Results: Five eligible randomized clinical trials (RCTs) were selected for the meta-analysis of M72/AS01E candidate vaccines. The analysis revealed that the M72/AS01E subunit vaccine had an abundance of polyfunctional M72-specific CD4+ T cells [standardized mean difference (SMD) = 2.37] in the vaccine group versus the control group, the highest seropositivity rate [relative risk (RR) = 5.09]. The M72/AS01E vaccinated group were found to be at high risk of local injection site redness (RR = 2.64), headache (RR = 1.59), malaise (RR = 3.55), myalgia (RR = 2.27), fatigue (RR = 2.16), pain (RR = 3.99), swelling (RR = 5.09), and fever (RR = 2.04) compared to the control groups. The incidences of common adverse events of M72/AS01E were local injection site redness, headache, malaise, myalgia, fatigue, pain, swelling, fever, etc. Six eligible RCTs were selected for the meta-analysis on MVA85A candidate vaccines. The analysis revealed that the subunit vaccine MVA85A had a higher abundance of overall pooled proportion polyfunctional MVA85A-specific CD4+ T cells SMD = 2.41 in the vaccine group vs. the control group, with the highest seropositivity rate [estimation rate (ER) = 0.55]. The MVA85A vaccinated group were found to be at high risk of local injection site redness (ER = 0.55), headache (ER = 0.40), malaise (ER = 0.29), pain (ER = 0.54), myalgia (ER = 0.31), and fever (ER = 0.20). The incidences of common adverse events of MVA85A were local injection site redness, headache, malaise, pain, myalgia, fever, etc. Conclusion: The M72/AS01E and MVA85A vaccines against TB are safe and had immunogenicity in diverse clinical trials. The M72/AS01E and MVA85A vaccines are associated with a mild adverse reaction. The meta-analysis on immunogenicity and safety of M72/AS01E and MVA85A vaccines provides useful information for the evaluation of available subunit vaccines in the clinic.